2020
DOI: 10.5006/3472
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Loading Spectra on High pH Crack Growth Behavior of X65 Pipeline Steel

Abstract: The effects of mechanical factors on crack growth behavior during the second stage of high pH stress corrosion cracking in pipeline steel were investigated by applying several loading scenarios on compact tension (CT) specimens. The main mechanism for stage 2 of intergranular crack propagation is anodic dissolution ahead of the crack tip which is highly dependent on crack-tip strain rate. The maximum and minimum crack growth rates were 3 × 10−7 mm/s and 1 × 10−7 mm/s, respectively. It was observed that several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The authors' previous work has demonstrated intergranular cracking under the test conditions using potentiodynamic polarization tests at two scan rates. 30 The corrosion fatigue tests started 24 h after setting up the test cell to allow the cell to reach equilibrium in temperature and potential. It is worth mentioning that a black film covered the side faces the CT specimens after 24 h of exposure to the test environment.…”
Section: Materials and Environmentmentioning
confidence: 99%
See 3 more Smart Citations
“…The authors' previous work has demonstrated intergranular cracking under the test conditions using potentiodynamic polarization tests at two scan rates. 30 The corrosion fatigue tests started 24 h after setting up the test cell to allow the cell to reach equilibrium in temperature and potential. It is worth mentioning that a black film covered the side faces the CT specimens after 24 h of exposure to the test environment.…”
Section: Materials and Environmentmentioning
confidence: 99%
“…Second, the differences between the fast and slow scan rate must be greater than one order of magnitude. 28,30,35,[41][42] According to Figure 4, the HpHSCC potential range is between −625 mV SCE and −575 mV SCE .…”
Section: Electrochemical Response Of the Steel In The Test Solutionmentioning
confidence: 99%
See 2 more Smart Citations
“…High pH-SCC usually occurs in a concentrated carbonate/bicarbonate electrolyte resulting in an intergranular cracking mode. The mechanism of high pH SCC is attributed to anodic dissolution resulting from selective dissolution at the grain boundary and repeated rupture of passivating film that form over the crack tip [ 10 ]. On the other hand, the occurrence of near-neutral pH SCC is associated with a special environment characterized with anaerobic, dilute bicarbonate solutions and the stress corrosion crack has a transgranular, quasi-cleavage crack morphology [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%